Website Quality, Store Image and Customer Satisfaction of E-Commerce in Myanmar - Htet, Atar Thaung (Asean International Journal of Business, 2025)
This study intends to analyze the effect of website quality and store image on customer satisfaction with e-commerce in Myanmar. Methodology The convivence sampling method was applied in this study. The 175 participants involved in this research process.The majority of the participants live in Yangon city which largest commercial city in Myanmar. The survey method is a major research strategy for this study, with a well-designed, structured questi onnaire. The descriptive statistics, Pearson correlation test and multiple linear regression test used for analysis the collected data. Findings – The major findings of this study are that system quality, service quality, and store image have a positive and significant effect on customer satisfaction. Novelty/value – Based on this finding, some suggestions were made for the practical and academic fields. The web creators and marketers should align the tech factors and non tech factors in order to create the more quality e-commerce sites in Myanmar market which are infant industry for e-business. The origin of this research is store image, which is considered another antecedent factor for determining the success of the information system (IS) model (customer satisfaction).